British children's performance on the listening in spatialised noise-sentences test (LISN-S). (2nd November 2019) - Murphy, C. F. B.; Hashim, E.; Dillon, H.; Bamiou, D. E.
Abstract: Objective: To investigate whether British children's performance is equivalent to North American norms on the listening in spatialised noise-sentences test (LiSN-S). Design: Prospective study comparing the performance of a single British group of children to North-American norms on the LiSN-S (North American version). Study sample: The British group was composed of 46 typically developing children, aged 6–11 years 11 months, from a mainstream primary school in London. Results: No significant difference was observed between the British's group performance and the North-American norms for Low-cue, High-cue, Spatial Advantage and Total Advantage measure. The British group presented a significantly lower performance only for Talker Advantage measure (z-score: 0.35, 95% confidence interval −0.12 to −0.59). Age was significantly correlated with all unstandardised measures. Conclusion: Our results indicate that, when assessing British children, it would be appropriate to add a corrective factor of 0.35 to the z-score value obtained for the Talker Advantage in order to compare it to the North-American norms. This strategy would enable the use of LiSN-S in the UK to assess auditory stream segregation based on spatial cues.